Using Communication to Modulate Neural Synchronization in Teams - Dunbar, Terri A.; Gorman, Jamie C. (Frontiers in Human Neuroscience, 2020)
Throughout training and team performance, teams may be assessed based on their communication patterns to identify which behaviors contributed to the team’s performance; however, this process of establishing meaning in communication is burdensome and time consuming despite the low monetary cost. A current topic in team research is developing covert measures, which are easier to analyze in real-time, to identify team processes as they occur during team performance; however, little is known about how overt and covert measures of team process relate to one another. In this study, we investigated the relationship between overt (communication) and covert (neural) measures of team process by manipulating the interaction partner (participant or experimenter) team members worked with and the type of task (decision-making or action based) teams performed to assess their effects on team neural synchronization (measured as neurodynamic entropy) and communication (measured as both flow and content). The results indicated that the type of task affected how the teams dynamically structured their communication but had unpredictable effects on the neural synchronization of the team when averaged across the task session. The interaction partner had no effect on team neural synchronization when averaged. However, there were significant relationships when communication and neural processes were examined over time between the neurodynamic entropy and the communication flow time series due to both the type of task and the interaction partner. Specifically, significant relationships across time were observed when participants were interacting with the other participant, during the second task trial, and across different areas of the cortex in the alpha and beta frequency ranges depending on the type of task being performed. The findings from the time series analysis suggest that factors previously known to affect communication dynamics (interaction partner and task type) also structure the relationship between team communication and neural synchronization, but only when examined across time. Future research should consider these factors when developing both overt and covert measures of team process for measuring team performance over time.